INFLUENCE OF ESSENTIAL FATTY ACIDS ON FAT METABOLISM AND MICROBIOCENOSIS IN ANIMALS FED WITH LEAN DIET - Levchenko, Ye. M. (Journal of Education, Health and Sport, 2015)
Levchenko Ye. M. Влияние незаменимых жирных кислот на жировой обмен и микробиоценоз у животных на безжировом рационе = Influence of essential fatty acids on fat metabolism and microbiocenosis in animals fed with lean diet. Journal of Education, Health and Sport. 2015;5(12):73-83. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35003 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A73-83 http://pbn.nauka.gov.pl/works/676642 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 30.11.2015. УДК 612.397.23+577.16+613.2 ВЛИЯНИЕ НЕЗАМЕНИМЫХ ЖИРНЫХ КИСЛОТ НА ЖИРОВОЙ ОБМЕН И МИКРОБИОЦЕНОЗ У ЖИВОТНЫХ НА БЕЗЖИРОВОМ РАЦИОНЕ INFLUENCE OF ESSENTIAL FATTY ACIDS ON FAT METABOLISM AND MICROBIOCENOSIS IN ANIMALS FED WITH LEAN DIET Е. М. Левченко Ye. M. Levchenko ГУ «Институт стоматологии НАМН Украины» (г. Одесса, Украина) The Institute of Stomatology of the National acfdemie of medical science of Ukraine (Odessa, Ukraine) Abstract Aim: To determine the state of lipid metabolism and microbiocenosis in rats receiving the drug containing essential fatty acids. Methods: We used the drug "Liposan" (vitamin F) containing 5 essential fatty acids: linoleic, linolenic, arachidonic, eicosapentaenoic, docosahexaenoic. The drug was administered to rats in the lean diet (B. Eggum, 1977) in the amount of 2.5% instead of the same amount of starch. Rats (male, 4 months old) received30 gof the diet daily. The duration of the experiment was 31 days. Triglycerides and total cholesterol were determined in the liver and the serum by enzymatic methods. Microbial contamination was judged by the urease activity, the state of nonspecific immunity (the lysozyme activity), the presence of inflammation (the elastase activity). The degree of dysbiosis by Levitsky was calculated as the ratio of the relative activities of urease and lysozyme. Results: In rats that received the fat-free diet (FFD) the triglyceride content and the degree of dysbiosis were increased in the liver and cholesterol was decreased in the serum. The addition of the drug "Liposan" reduced the degree of dysbiosis in the liver but did not alter lipid metabolism. Conclusion: "Liposan" can be used as an anti-dysbiotic drug, especially for people who are prone to obesity. Keywords: fat-free diet, essential fatty acids, liver, serum, triglycerides, cholesterol, dysbiosis. Резюме Препарат незаменимых жирных кислот «Липосан», содержащий линолевую, линоленовую, арахидоновую, эйкозапентаеновую и докозагексаеновую кислоты, при вводе в состав безжирового рациона в количестве 2,5 % снижает степень дисбиоза в печени до нормы и не увеличивает прирост живой массы и содержание липидов в печени и сыворотке крови. Ключевые слова: безжировой рацион, незаменимые жирные кислоты, печень, сыворотка крови, триглицериды, холестерин, дисбиоз.